Recent Findings in Intelligent Computing Techniques Proceedings of the 5th ICACNI 2017, Volume 3 - Sa, Pankaj Kumar; Bakshi, Sambit; Hatzilygeroudis, Ioannis K.; Sahoo, Manmath Narayan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This three volume book contains the Proceedings of 5th International Conference on Advanced Computing, Networking and Informatics (ICACNI 2017). The book focuses on the recent advancement of the broad areas of advanced computing, networking and informatics. It also includes novel approaches devised by researchers from across the globe. This book brings together academic scientists, professors, research scholars and students to share and disseminate information on knowledge and scientific research works related to computing, networking, and informatics to discuss the practical challenges encountered and the solutions adopted. The book also promotes translation of basic research into applied investigation and convert applied investigation into practice.
Preface -- Foreword -- Organizing Committee Details -- In memoriam Prof. S.K. Jena -- Table of Contents -- 60 Papers -- Author Index.
Keywords: Computational intelligence; Artificial intelligence; Telecommunication; Computational Intelligence; Artificial Intelligence; Communications Engineering, Networks